Drug repurposing against Candida auris: A systematic review. Issue 8 (19th June 2022) - Izadi, Alireza; Aghaei Gharehbolagh, Sanaz; Sadeghi, Fatemeh; Talebi, Meysam; Darmiani, Kimia; Zarrinnia, Ali; Zarei, Fateme; Peymaeei, Fatemeh; Khojasteh, Shaghayegh; Borman, Andrew M.; Mahmoudi, Shahram
Abstract: Candida auris is a drug‐resistant pathogen with several reported outbreaks. The treatment of C. auris infections is difficult due to a limited number of available antifungal drugs. Thus, finding alternative drugs through repurposing approaches would be clinically beneficial. A systematic search in PubMed, Scopus and Web of Science databases, as well as Google Scholar up to 1 November 2021, was conducted to find all articles with data regarding the antifungal activity of non‐antifungal drugs against the planktonic and biofilm forms of C. auris . During database and hand searching, 290 articles were found, of which 13 were eligible for inclusion in the present study. Planktonic and biofilm forms have been studied in 11 and 8 articles (with both forms examined in 6 articles), respectively. In total, 22 and 12 drugs/compounds have been reported as repositionable against planktonic and biofilm forms of C. auris, respectively. Antiparasitic drugs, with the dominance of miltefosine, were the most common repurposed drugs against both forms of C. auris, followed by anticancer drugs (e.g. alexidine dihydrochloride) against the planktonic form and anti‐inflammatory drugs (e.g. ebselen) against the biofilm form of the fungus. A collection of other drugs from various classes have also shown promising activity against C. auris . Following drug repurposing approaches, a number of drugs/compounds from various classes have been found to inhibit the planktonic and biofilm forms of C. auris . Accordingly, drug repurposing is an encouraging approach for discovering potential alternatives to conventional antifungal agents to combat drug resistance in fungi, especially C. auris .